BUDAYA TRI HITA KARANA SEBAGAI PEMODERASI PENGARUH PENGANGGARAN PARTISIPATIF, PENGENDALIAN ANGGARAN DAN STANDAR OPERASIONAL PROSEDUR PADA PERILAKU DISFUNGSIONAL - Yudastri, Ni Ketut; Budiartha, I Ketut; Badera, I Dewa Nyoman (Buletin Studi Ekonomi; VOL.22.NO.1. FEBRUARI 2017 (PP 1-112)DO - 10.24843/bse.2017.v22.i01.p09, 2017)
Dysfunctional behavior is deviant behavior or violations of the rules and procedures of managerial control system of local government is done deliberately by officials themselves. The purpose of this study was to examine the influence of participatory budgeting, budget control and standard operating procedures (SOP) on dysfunctional behaviors and examines cultural influences as pemoderasinya Tri Hita Karana. The sample was 36 SKPD in Gianyar regency government with 102 respondents consisting of structural officials directly involved in the budgeting process. Data analysis was performed using Moderated Regression Analysis (MRA). The results of this study are participatory budgeting and budgetary control positive effect on dysfunctional behavior. Standard operating procedure has no effect on dysfunctional behavior. Tri Hita Karana Cultural weaken the influence of participatory budgeting and control angggaran on dysfunctional behavior. Culture Tri Hita Karana not moderate influence on the standard operating procedures dysfunctional behavior.